The effectiveness of a program based on the multisensory approach in improving the working memory of students with learning disabilities - Aram Karim Ahmed; Afrah Yaseen Mohammed Al-Dabbagh (Zanco Journal of Humanity Sciences)
The aims of the current research are to reveal the effectiveness of a training program based on the Approach Multisensory and work on improving the working memory of children with learning difficulties, and as well as verifying the size of the effect, The researchers used the experimental approach, with a pre- and post-measurement of the experimental group.